PENGARUH KOMPENSASI, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PARA PEGAWAI BADAN PENANGGULANGAN BENCANA PROVINSI SUMATERA SELATAN - OKTRIANA VERTASARI; ZUNAIDAH . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The study conducted to look at the effect of compensation, competences and working environmentÂ  toward the job performance of the employees of Disaster Management Agency of South Sumatra Province (BPBD Sumatera Selatan), aims to identify (a) to investigate partially influences of compensation, competency and working environment affecting the job performance of the employees of Disaster Management Agency of South Sumatera Province (BPBD Sumatera Selatan), (b) to investigate simultantly influences of compensation, competency and working environment affecting the job perofmance of the employees of Disaster Management Agency of South Sumatera Province (BPBD Sumatera Selatan), (c) to investigate which variable have dominant affecting the job performance.The method used in this study was causal method. The random sampel by using non probability with numbers of the population are 76, The technique of data collection was using questionnaries.The research finding shows partially compensation, competency a influence on job performance but working environment doesnâ€™t influence it, simultantly compensation, competency and working environment influence on job performance of Disaster Management Agency of South Sumatra Province (BPBD Sumatera Selatan), Competency has dominant influence on employees job performance of Disaster Management of Disaster Management Agency of South Sumatera Province (BPBD Sumatera Selatan.